Acute lung injury timely associated with the administration of tocilizumab - Hočevar, Alojzija; Srpčič, Anja; Lakota, Katja; Fister, Miša (Reumatismo, 2026)
Dear editor,The interleukin-6 receptor inhibitor tocilizumab has been successfully used to treat various autoimmune diseases and has an acceptable, well-established safety profile...
Keywords: Tocilizumab; adverse drug reaction; acute lung injury